Creative individualism the democratic vision of C. B. Macpherson - Lindsay, Peter (State Univ. of New York Press, 1996)
Starting with C.B. Macpherson's conception of human nature and working through his idea of a just society, Peter Lindsay constructs a cohesive picture of Macpherson's democratic vision - a task Macpherson himself never undertook. Lindsay argues that Macpherson's central message regarding the importance of economic equality for democracy is as relevant today as it was when first presented. In addition to offering a detailed picture of the economic prerequisites for democracy, Lindsay presents Macpherson's particular brand of liberal democracy as one that offers valuable insights into contemporary democratic and liberal debates. The result is a vision of creative individualism for the post-communist world that combines Macpherson's insistence on social justice with the lessons learned from failed attempts at central planning.
Keywords: Macpherson, C. B <1911-1987> -- (Crawford Brough); Macpherson, Crawford B. -- 1911-1987; Democracy; Social justice; Demokratie